Cooperative learning for the transfer of MIAF technology: the mixes of Oaxaca - Martínez Gómez, Gladys; Santos Corral, María Josefa; de Gortari Rabiela, Rebeca Nadia; Romo Lozano, José Luis; Martínez, Daniel Vega (Revista Mexicana de Ciencias Agrícolas, 2021)
This work is part of a larger study whose purpose was to understand the practices of small farmers for caring for the environment. The objective of this study is to analyze cooperative learning, a form of socio-cultural learning among small farmers Aayujk, Mixe community of the municipality of Santa Maria Tlahuitoltepec, Oaxaca in Mexico. The exchange of knowledge and symbolic references during the transfer of agricultural technological packages generate diverse learning, including cooperative learning. This research is qualitative, with the application of the ethnographic method that involves direct observations as units of inductive analysis, as well as interviews with producers. Based on the results, it was found that traditional forms of social organization reinforce cooperative learning. Small farmers conclude that mutual support and learning facilitate their agricultural work, incur lower expenses, obtain products for their own consumption and enhance their marketing.
Keywords: soil conservation; MIAF; southeast Mexico.